Students' academic performance by using e-learning as a method of teaching and learning / Mohd Faizul Hassan and Naffisah Mohd Hassan - Hassan, Mohd Faizul; Mohd Hassan, Naffisah (UiTM Press, 2024)
E-learning is being implemented in higher educational institutions as a method of teaching and learning. Several studies have been carried out on academic performance, particularly on a group of conventional students. However, only a few have been written on E-learning among PJJ students' academic performance in E-learning technology. This study was conducted to determine and investigate the relationship between Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) towards Attitude (ATT) and Actual Use (AU) as a factor of Students' Academic Performance towards e- learning technology among students of the business management faculty enrolled in BA232 Bachelor in Office Systems Management (Hons) at UiTM Puncak Alam. This study took a quantitative and stratified sampling approach with 155 respondents. Statistical methods analyses used were multiple regression and logistic regression. Actual Use (AU), Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude (ATT), and Actual Use (AU) are significant as the p-values are smaller than = 0.05. E-learning use had a significant influence on students' academic performance. Thus, the more the students use E-learning, the better their academic performance. This study would benefit online institutions, online / distance instructors, decision-makers at all higher education levels, and online students. The implications for practices, barriers to e-learning, ongoing support by the government, limitations of the study and recommendations for research were discussed.